Avaliação de cenários com as alterações do plano de mobilidade urbana através de simulação: caso de uso para a cidade de Santa Maria - Silva, Marina Laisa Mota da (2022)
Due to events (football games, accidents, college entrance exams, etc.), seasonality, or even to adjust mobility demand due current load and further expansions, many city halls need to rethink transportation system in cities. Changes can include the rotation of vehicles, augmentation of the fee payment values and cost of parking tickets or limiting the number of vehicles in circulation. Anyway, changes in the transportation system in cities are always continuously necessary to guarantee the adequate urban mobility. Before proposing changes to the real urban transport system, in order to solve the listed problems, it is necessary to evaluate the improvements that these solutions propose concerning the system currently implemented. Computer simulation opens a new opportunity in this scope. Thus, this work proposes the evaluation of different infrastructure scenarios, with computer simulation support, and their impact on traffic to the urban transportation system. As use case, the down town of the City of Santa Maria, in Southern Brazil is used. The assessed scenarios reflect the improvements to the Urban Mobility Plan (UMP) defined by the city authorities. Simulation support is provided by SUMO. One of the big challenges of this work is the lack of data about city traffic. So, the simulation was calibrated using information available in the prefecture and in Internet news. More specifically, in this thesis: (a) we model different city scenarios according to the current and future city UMP and (b) we evaluate these scenarios in a simulation environment with regard to pollutant emissions, traveled distance and travel time.